Existing Classroom Teaching Practices in Janamaitri Multiple Campus, Kuleshwar - Singh, Dipak; Tripathi, Ramesh (JMC Research Journal, 2023)
The present study has conducted with the main objective to access the classroom teaching practices by the teachers. It has followed the personal status of the teachers as well as the practices of effective classroom teaching. It was based on observational descriptive research design with quantitative nature. The study was conducted on Janamaitri Multiple Campus and the full-time faculties with in the campus. The purposive sampling technique was applied to select the 30 faculties including of 20 male and 10 female faculties. The direct class observation was applied to collect the data and information with major components for effective teaching learning activities. The study concludes that there is normal gap between male and female teachers in teaching profession, most of the teachers were in the middle age group, most of the male teachers had only master level of education except female teachers, most of the teachers had excellent teaching experience from ten to twenty-five years and all most all the teachers had salary as a main source of personal income. Some teachers got regular teaching training in their respective subjects, only few teachers had followed the structured lesson plans and strategy during teaching learning, some teachers had followed traditional methods of teaching and materials during teaching and most of the teachers had managed the classroom properly during teaching learning activities. The regular training and refresher program regarding of modern teaching techniques should be conducted by the campus administration for their respected teachers. Regular monitoring and discussion session with teachers, students and administration should be conducted for improvement.